INSTRUMEN UNTUK MENJARING DATA INTERVAL. NOMINAL, ORDINAL DAN DATA TENTANG KONDISI, KEADAAN, HAL TERTENTU DAN DATA UNTUK MENJARING VARIABEL KEPRIBADIAN - WINDIYANI, TUSTIYANA (JURNAL PENDIDIKAN DASAR, 2012)
This article is talking about types of measurement in order to meazure some variabels which has interval, nominal, ordinal data, as well as variabels which are talking about a condition, an existence and an event. Else, this article also gives some statements about meazuring an attitude of a person.